Agaricaceae and Psathyrellaceae from Suranadi Natural Park in Lombok Island - Meilinda Pahriana Sulastri; Hasan Basri (LOMBOK JOURNAL OF SCIENCE, 2021)
Fungi is one of the important organisms in ecosystem. Most macrofungi are composed of fungalspecies from the division Basidiomycota and some belong to the division Ascomycota. Macrofungihas a role in ecosystem by decomposing materials that contribute to carbon cycling. Mycorrhizalmacrofungi organize nitrogen and phosphorus to support the other species in forest ecosystem.Additionally, some species of macrofungi are important food source and medicine. Agaricaceaeis one of the most diverse families of fungi. Most of the species are cosmopolitan and saprotrophsthat grow in dead wood, trees, log and leaf litter. The species of Agaricaceae have variety of morphology. Psathyrellaceae are a family of fungal species with dark spores. The member of thefamily generally has soft and fragile fruit body dissolve by autodigestion. This study aims to identify the macrofungi belong to family Agaricaceae that grow in Suranadi Natural Park. This is descriptive explotative study by exploring and describing the species of Agaricaceae andPsathyrellaceae found in Suranadi Natural Park. Sampling was carried out using the cruisemethod. The fungal sample found was documented and observed. Identification was carried outby matching the morphological characters of fungal sample and environmental conditions usingthe reference book and various scientific journals on Agaricaceae and Psathyrellaceae species.The identification results found 1 species of Agaricaceae including Lepiota sp. and 2 species of Psathyrellaceae i.e. Coprinellus sp. and Parasola sp.